Multi-component alloys
Patent Information
- Application Number
- JP2022530120
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-10
- Filing Date
- 2021-05-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-05-26
AI Technical Summary
【0019】 本発明の多成分系からなる合金によれば、高強度、高延性を有する多成分系からなる合金を提供できるという有利な効果を奏する。また、別の態様によれば、本発明の多成分系からなる合金は、生体適合性にも優れるため、生体適合性材料としても使用できるという有利な効果を奏する。
Smart Images

Figure 0007943633000003 
Figure 0007943633000004 
Figure 0007943633000005
Abstract
Description
[Technical Field]
[0001] The present invention relates to a multi-component alloy, a biocompatible material made from the alloy, and a method for manufacturing the alloy, and more particularly to a multi-component alloy having high strength and high ductility, a biocompatible material made from the alloy, and a method for manufacturing the alloy. [Background technology]
[0002] To meet the diverse needs of various applications, we have been striving to improve the mechanical properties of metal materials by working on improvements based on existing alloys. For example, we have developed high-strength materials ranging from biomedical materials such as bone implants to metal materials requiring durability in chemical plants and other applications.
[0003] On the other hand, conventional alloys are mainly those with a single element as the main alloying element, but recently, multi-component alloys such as hydrogen storage alloys have also been developed. For example, a hydrogen storage alloy is known that is represented by the general formula TixVyMzNi1-xyz (where M is at least one element selected from the group consisting of Al, Mn, and Zn, and 0.2≦x≦0.4, 0.3≦y<0.7, 0.1≦z≦0.3, 0.6≦x+y+z≦0.95), in which the main component of the alloy phase has a body-centered cubic structure (Patent Document 1). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 09-053136 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, conventional alloys, including those mentioned above, have faced limitations in their properties in order to meet a wide variety of applications. This is because, in typical alloy design, alloys are often composed of a single element or two elements as the main elements, with only small amounts of other elements, and therefore have problems such as not being able to dramatically improve existing alloy properties.
[0006] For example, in Japan, which is facing a super-aging society, the increasing importance of bone implants has led to a demand for the development of high-performance biocompatible metal materials for bone. Currently, titanium and titanium alloys are used as biocompatible metal materials from the perspective of mechanical reliability and biocompatibility. However, in addition to the required mechanical functions, there are many hurdles to overcome when considering in-vivo use, such as biocompatibility. To further improve the mechanical performance of biocompatible metal materials, it is no longer possible to make significant improvements based on existing alloys, and we are facing a situation where the development of alloys based on entirely new design philosophies is required.
[0007] Furthermore, materials and components used in chemical plants, oil wells, and gas well drilling equipment are exposed to highly corrosive gases, requiring higher strength and corrosion resistance. For these reasons, the development of new alloys with higher strength has been desired.
[0008] Therefore, the present invention aims to provide a multi-component alloy having high strength and high ductility. [Means for solving the problem]
[0009] To achieve the above objective, the inventors diligently researched various compositions in order to induce entropy effects in configurations that do not normally appear in conventional alloys, and as a result, discovered the multi-component alloy of the present invention.
[0010] In other words, the multi-component alloy of the present invention consists of titanium, zirconium, niobium, and molybdenum. 、 tantalum , and containing hafniumThe alloy is a multi-component alloy (excluding tungsten and vanadium), and the alloy is composed of Mo equivalents (where Mo equivalent = [Mo] + 0.26[Au] + 0.43[Bi] + 12.62[Be] + 2.93[Co] + 1.65[Cr] + 0.85[Cu] + 4.17[Fe] + 0.05[Hf] + 0.17[Mg] + 3.28[Mn] + 0.64[Nb] + 1.75[Ni] + 0.23[Os] + 0.71[Pd] + 0.64[Pt] + 0.29[Pu] + 1.72[Re] + 2.89[Rh] + 1.67[Ru] + 0.97[Si] + 0.23[Ta] + The alloy satisfies 0.32[U]+ 0.80[V]+ 0.56[W]+ 1.13[Y]+ 0.16[Zr])≧13.5, and the alloy is a multi-component system consisting of a single-phase solid solution, a two-phase solid solution, or a solid solution phase as the main phase, and the alloy satisfies the condition 1.5R≦ΔSmix (where R is the gas constant and ΔSmix is the configurational entropy), and is a multi-component system satisfying -15≦Hmix, 7≧δ, 4.7≧VEC (where Hmix is the mixing enthalpy, δ is the atomic radius ratio factor and VEC is the valence electron concentration), and the alloy has the general formula: (TiZrHf) X (NbTa) Y Mo 100-X-Y It is characterized by being shown as (where 57.2 ≤ X ≤ 85 and 12.8 ≤ Y ≤ 33.3; and the values in parentheses indicate the presence of the element in parentheses).
[0012] Furthermore, in a preferred embodiment of the multi-component alloy of the present invention, the alloy is characterized in that it satisfies a VEC value (valence electron concentration) ≤ 4.7.
[0013] Furthermore, in a preferred embodiment of the multi-component alloy of the present invention, the alloy is characterized by containing a BCC structure.
[0016] Furthermore, the biocompatible material of the present invention is characterized by being composed of the alloy of the present invention.
[0017] Furthermore, the method for producing a multi-component alloy according to the present invention is a method for producing a multi-component alloy according to the present invention, characterized in that it includes a step of melting the alloy by a method selected from a rapid solidification method, a vacuum arc melting method, a casting method, a melting method, a three-dimensional additive manufacturing method, or a powder metallurgy method.
[0018] Furthermore, a preferred embodiment of the method for producing a multi-component alloy of the present invention is characterized by further including a step of annealing the alloy. [Effects of the Invention]
[0019] The multi-component alloy of the present invention offers the advantageous effect of providing a multi-component alloy with high strength and high ductility. Furthermore, according to another embodiment, the multi-component alloy of the present invention also exhibits excellent biocompatibility, thus offering the advantageous effect of being usable as a biocompatible material. [Brief explanation of the drawing]
[0020] [Figure 1] Figure 1 shows the new alloy parameters, the ground phase diagram constructed based on the first-principles calculation database, and the results of thermodynamic calculations (CALPHAD). Specifically, Figure 1 shows the alloy design of the non-isoatomic composition ratio Ti-Zr-Hf-Nb-Ta-Mo bioHEA, Figure 1(a) shows the relationship between the alloy parameters and the BCC / HCP structure, Figure 1(b) shows the ground phase diagram constructed by the Materials Project, and Figure 1(c) shows the equilibrium calculation results obtained by FactSage and SGTE2017. Indices Eq, 1, 2, and 3 correspond to TZHNTM-X (X = Eq, 1, 2, 3). [Figure 2]Figure 2 shows the microstructure observation results of arc-melted ingots in the equiatomic composition ratio TiNbTaZrMo (TZHNTM-Eq) alloy and the non-equiatomic composition ratio Ti28.32Zr28.32Hf28.32Nb6.74Ta6.74Mo1.55 (TZHNTM-3) alloy. Figure 2(a) shows the XRD pattern, and Figure 2(b) shows the SEM-BSE image and EDS element mapping focusing on Ti and Zr, respectively. [Figure 3] Figure 3 shows the room temperature tensile test results (true stress-plastic strain diagram) of the arc-melted ingot of the non-equiatomic composition ratio Ti28.32Zr28.32Hf28.32Nb6.74Ta6.74Mo1.55 (TZHNTM-3) alloy. [Figure 4] Figure 4 shows the biocompatibility evaluation results of the arc-melted ingot of the non-equiatomic composition ratio Ti28.32Zr28.32Hf28.32Nb6.74Ta6.74Mo1.55 (TZHNTM-3) alloy. Reference materials are SUS-316L stainless steel, Co-Cr-Mo alloy (ASTM F1537-08), and CP-Ti. Figure 4(a) shows the quantitative analysis result of the number of cell adhesions based on Giemsa-stained images, and Figure 4(b) shows the fluorescence-stained image of cell morphology on the material surface, respectively. [Figure 5] Figure 5 shows the results of observing the crystal structure of the obtained alloy by XRD. [Figure 6] Figure 6 shows a backscattered electron image of the obtained alloy observed by a scanning electron microscope. That is, it shows that an equiaxed dendrite structure characteristic of high-entropy alloys is observed in the obtained alloy. [Figure 7] Figure 7 shows the tensile test results for the as-cast material and the heat-treated material. [Figure 8] Figure 8 shows the observation results by Giemsa staining and immunostaining, and specifically shows the biocompatibility results for the as-cast material and the heat-treated material. [Mode for Carrying Out the Invention]
[0021] The multi-component alloy of the present invention is a multi-component alloy containing titanium, zirconium, niobium, molybdenum, and tantalum, and further comprising at least one selected from the group consisting of hafnium, tungsten, vanadium, and chromium, wherein the alloy satisfies Mo equivalent ≥ 13.5, and the alloy is a single-phase solid solution, a two-phase solid solution, or the main phase is a solid solution phase. In the present invention, the alloy is characterized by satisfying Mo equivalent ≥ 13.5 from the viewpoint of high ductility. In the present invention, for the Mo equivalent (Moeq), formula (1) proposed by Kiyohito Ishida based on the thermodynamic database of Ti alloys was used. Moeq is given by the following formula (1) (Scheffler phase diagram of Ti-based alloy).
[0022] Moeq =[Mo]+ 0.26[Au]+ 0.43[Bi]+ 12.62[Be]+ 2.93[Co]+ 1.65[Cr]+ 0.85[Cu]+ 4.17[Fe]+0.05[Hf]+0.17[Mg]+ 3.28[Mn]+ 0.64[Nb]+ 1.75[Ni]+ 0.23[Os]+ 0.71[Pd]+ 0.64[Pt]+ 0.29[Pu]+ 1.72[Re]+ 2.89[Rh]+ 1.67[Ru]+ 0.97[Si]+ 0.23[Ta]+ 0.32[U]+ 0.80[V]+ 0.56[W]+ 1.13[Y]+ 0.16[Zr](1)
[0023] Furthermore, the alloy of the present invention is a single-phase solid solution, a two-phase solid solution, or a solid solution phase as the main phase. In other words, the alloy of the present invention can be said to be a so-called high-entropy alloy (hereinafter also referred to as HEA) that exhibits an entropy effect in a configuration that does not normally appear in conventional alloys. The alloy of the present invention preferably consists of a pentagonal system or a multi-component system of 5 or more elements, and from the viewpoint of the effects of ΔSmix and ΔHmix, the composition of each constituent element can preferably be 0.1 to 35 at%, more preferably 7 to 25 at%, and even more preferably 10 to 22 at%.
[0024] The difference between the high-entropy alloy of the present invention and other multi-component alloys is that the high-entropy alloy is a single-phase solid solution, a two-phase solid solution, or has a solid solution phase as its main phase, and has high mixing entropy.
[0025] The alloy of the present invention is a high-entropy alloy (hereinafter referred to as HEA) that exhibits high strength, high ductility, low Young's modulus, heat resistance, and other special properties despite being a solid solution with a simple crystal structure, by maximizing the configurational entropy effect that does not normally appear in conventional alloys. In addition, the present invention makes it possible to impart biocompatibility. Furthermore, the present invention is innovative in that, in the search for alloy compositions in which HEA exists, a systematic alloy development method for HEA alloys applicable to biomedical use has been established, using configurational entropy (ΔSmix), mixing enthalpy (ΔHmix), atomic radius ratio factor (δ parameter), valence electron concentration (VEC parameter), and, if necessary, biotoxicity of the constituent elements as parameters. In the present invention, by complexly arranging different atomic species in the high-entropy alloy, it is possible to bring out several beneficial characteristics that differ from general alloys. For example, features include improved ductility due to solid solution formation and increased strength due to a strained lattice.
[0026] The principle of this invention is as follows: HEA requires selecting a composition in which the constituent elements are increased and the entropy effect of the arrangement is maximized. In this invention, while giving the utmost importance to the condition 1.5R ≤ ΔSmix (where R is the gas constant), it was found that HEA can be obtained in a composition that satisfies -15 ≤ ΔHmix and 7 ≥ δ.
[0027] Furthermore, in a preferred embodiment of the multi-component alloy of the present invention, the alloy is characterized by containing titanium, zirconium, niobium, molybdenum, tantalum, and hafnium. In another preferred embodiment, the alloy is characterized by satisfying a VEC value (valence electron concentration) ≤ 4.7 from the viewpoint of high ductility.
[0028] Furthermore, in a preferred embodiment of the multi-component alloy of the present invention, the alloy is characterized by including a BCC structure from the viewpoint of achieving high ductility.
[0029] Furthermore, in a preferred embodiment of the multi-component alloy of the present invention, the alloy is characterized by the general formula: (TiZrHf) X (NbTaMo) 100-X The following is a characteristic of the formula shown (where 57.2 ≤ X ≤ 85). In the above general formula, there are no particular limitations as long as -15 ≤ ΔHmix, 7 ≥ δ, and 4.7 ≥ VEC are satisfied, but from the viewpoint of a composition range in which high properties can be expected from alloy design based on the entropy of the mixture (ΔSmix), Mo equivalent, and VEC, the range of x can preferably be 57.2 ≤ X ≤ 85, more preferably 70 (70% titanium group) ≤ X ≤ 85, and even more preferably 78.1 ≤ X ≤ 85.
[0030] Furthermore, in a preferred embodiment of the multi-component alloy of the present invention, the alloy is characterized by the general formula: (TiZrHf) X (NbTa) Y Mo 100-X-Y The formula is characterized by the expression shown above (where 57.2≦X≦85 and 12.8≦Y≦33.3). In the above general formula, there are no particular limitations as long as -15≦ΔHmix, 7≧δ, and 4.7≧VEC are satisfied, but from the viewpoint of a composition range in which high properties can be expected from alloy design based on the entropy of the mixture (ΔSmix), Mo equivalent, and VEC, the range of X can preferably be 57.2≦X≦85, more preferably 70 (70% titanium group)≦X≦85, and even more preferably 78.1≦X≦85, and the range of Y can preferably be 12.8≦Y≦33.3, more preferably 12.8≦Y≦20 (20 for Nb and Ta), and even more preferably 12.8≦Y≦13.5. The approach to expressing the composition of these alloys involves: 1) classifying elements into three groups based on Ti, Zr, Hf (VEC=4) and Nb, Ta (VEC=5), Mo (VEC=6) to lower the VEC value; and 2) calculating the Mo equivalent by considering not only cases where the ratios of Ti, Zr, and Hf, and the ratios of Nb and Ta are the same but also cases where they are different. This allows for the discovery of a composition range that exhibits high properties and a greater entropy effect.
[0031] Furthermore, the biocompatible material of the present invention is characterized by comprising an alloy consisting of the multi-component system of the present invention. The above description can be directly applied to the alloy consisting of the multi-component system of the present invention. This is because, as will be clear from the examples described later, Ti, Zr, Nb, Ta, Mo, and Hf not only enabled the realization of a high-entropy alloy, but also exhibit low cytotoxicity and can fully function as a biocompatible material.
[0032] Furthermore, the method for producing a multi-component alloy according to the present invention can be described as follows. That is, the method for producing a multi-component alloy according to the present invention is characterized by including a step of melting the alloy by a method selected from rapid solidification, vacuum arc melting, casting, melting, three-dimensional additive manufacturing, or powder metallurgy, from the viewpoint of producing a uniform alloy.
[0033] Furthermore, in a preferred embodiment of the method for producing a multi-component alloy of the present invention, the method is characterized by further including a step of annealing the alloy, from the viewpoint of modifying the solidification structure. The temperature for the annealing treatment is preferably 100 to 1500°C, more preferably 800 to 1200°C, and even more preferably 950 to 1050°C, from the viewpoint of the diffusion coefficient of the constituent atoms. The time for the annealing treatment is preferably 5 minutes to 1 month, more preferably 24 hours to 10 days, and even more preferably 6 days to 8 days, from the viewpoint of the time to reach an equilibrium state. [Examples]
[0034] Herein, an embodiment of the present invention will be described, but the present invention is not to be interpreted as being limited to the following embodiment. Furthermore, it goes without saying that the present invention can be modified as appropriate without departing from the spirit of the invention.
[0035] Example 1 First, the isoatomic composition ratio TiZrHfNbTaMo HEA (Ti16.67Zr16.67Hf16.67Nb16.67Ta16.67Mo16.67 at%, hereafter referred to as TZHNTM-Eq) was used as the starting composition. Then, in order to develop a bio-HEA that ultimately exhibits room-temperature ductility, the following three policies were adopted: (1) to satisfy the entropy-based definition of HEA, the enthalpy of the mixture (ΔSmix) must be ΔSmix ≥ 1.5 R (where R is the gas constant); (2) to suppress macroscopic casting defects such as molten metal boundaries, the melting point must be lowered; and (3) the VEC value must be lowered. In order to design an unequal-atomic composition ratio Ti-Zr-Hf-Nb-Ta-Mo alloy, the TiB+AxZrB+AxHfB+AxNbB+AxTaB+AxMoB+Ax alloy was devised. Here, A is a parameter related to the melting point of the pure substance, B is a parameter related to the VEC of the pure substance, and x is a variable. To lower the melting point of the alloy, A is defined as A = (Tm - Tm (i)) / Tm. Here, Tm (i) is the melting point of the pure substance of element i, and Tm is given by the following formula.
[0036]
number
[0037]
number
[0038] Next, in order to simultaneously decrease the melting point and VEC, we considered the case where parameter B was set to the following values: B(Ti)=1.5, B(Zr)=1.5, B(Hf)=1.5, B(Nb)=1.25, B(Ta)=1.25, and B(Mo)=1. Parameter B can be considered by utilizing the VEC ratio relationship 6 : 5 : 4 = 1.5 : 1.25 : 1, and by lowering the overall VEC value of the alloy. When B(Ti, Zr, Hf) = 1.5, B(Nb, Ta) = 1.25, B(Mo) = 1, it was found that ΔSmix, compositional average melting point, and VEC all decreased monotonically with increasing x in the TiB+AxZrB+AxHfB+AxNbB+AxTaB+AxMoB+Ax alloy. As an alloy that satisfies the condition ΔSmix≧1.5R and minimizes the compositional average melting point and VEC, we have TiZr0.88Hf0.63Nb0.37Ta0.24Mo0.02 (Ti32.61Zr28.58Hf20.39Nb12.05 Ta5.57Mo0.80 We designed at%, hereafter TZHNTM-2). As an alloy considering only VEC and ignoring the melting point, we considered Tix1Zrx1Hfx1Nbx2Tax2Mox3.
[0039] Here, x1, x2, and x3 are variables. As an alloy that satisfies the condition ΔSmix≧1.5R while minimizing VEC, we designed TiZrHfNb0.24Ta0.24Mo0.05 (Ti28.33Zr28.33Hf28.33Nb6.74Ta6.74Mo1.55 at%, hereafter TZHNTM-3) with x1, x2, and x3 set to 1, 0.24, and 0.05, respectively. Equiatomic composition ratio TiZrHfNbTaMo (TZHNTM-Eq) alloy, and non-equitomic composition ratio Ti-Zr-Hf-Nb-Ta-Mo (TZHNTM-X, (X = 1, 2, 3) In all of the alloys, the empirical parameters of high-entropy alloys, ΔHmix (mixing enthalpy), Ω (omega parameter: a dimensionless parameter that includes both ΔSmix and ΔHmix and evaluates the relative relationship between ΔSmix and ΔHmix), and δ (atomic radius ratio factor), showed a high tendency for solid solution formation.
[0040] Example 2 Next, in order to further investigate the solid solution formation tendency and the crystal structure of the constituent phases, the crystal structure was examined using new alloy parameters, a ground phase diagram constructed based on a first-principles calculation database, and the results of thermodynamic calculations (CALPHAD). The results are shown in Figure 1. The VEC value is effective for predicting the structure of BCC / HCP and the ductility of cast materials. In this invention, the Mo equivalent (Moeq) was newly applied. Moeq was calculated using the formula proposed by Ishida based on a thermodynamic database of Ti alloys. Moeq is given by the following formula (1). Moeq =[Mo]+ 0.26[Au]+ 0.43[Bi]+ 12.62[Be]+ 2.93[Co]+ 1.65[Cr]+ 0.85[Cu]+ 4.17[Fe]+0.05[Hf]+0.17[Mg]+ 3.28[Mn]+ 0.64[Nb]+ 1.75[Ni]+ 0.23[Os]+ 0.71[Pd]+ 0.64[Pt]+ 0.29[Pu]+ 1.72[Re]+ 2.89[Rh]+ 1.67[Ru]+ 0.97[Si]+ 0.23[Ta]+ 0.32[U]+ 0.80[V]+ 0.56[W]+ 1.13[Y]+ 0.16[Zr](1)
[0041] Here, [M] is the mass fraction of component M. Figure 1a shows the crystal structures of biomedium-entropy alloys (bioMEA), bioHEA (○, □, ×), and the design alloy (TZHNTM-X (X = Eq, 1, 2, 3)) (●), organized by VEC and Moeq. Here, BCC (○ and ●), BCC+HCP (□), and HCP (×) are shown. The structures of bioMEA and bioHEA showed a tendency to change from BCC → BCC+HCP → HCP as the VEC (Figure 1a1) and Moeq (Figure 1a2) values decreased. In the figure organized by VEC value (Figure 1a1), BCC+HCP and BCC overlapped, but no overlap was observed in the figure organized by Moeq (Figure 1a2). This result indicates that Moeq is an excellent parameter, similar to VEC, for predicting the structure of bioMEA and bioHEA. Moeq and VEC do not have a one-to-one correspondence. Furthermore, it was found that there is no clear correlation between Moeq and the empirical parameters (ΔHmix, Ω, δ). In other words, Moeq can be treated as a parameter independent of the empirical parameters (ΔHmix, Ω, δ), and this characteristic is similar to that of VEC.
[0042] The ground phase diagrams predicted by the Materials Project (A. Jain, SP Ong, G. Hautier, W. Chen, WD Richards, S. Dacek, S. Cholia, D. Gunter, D. Skinner, G. Ceder, KA Persson, APL Materials, 1, 1 (2013) 011002.) have proven useful for the alloy design of ultra-multi-component alloys such as liquid-phase-separated amorphous alloys and high-entropy alloys. Figure 1b shows the ground phase diagrams at 0K constructed by the Materials Project. In the Ti-Zr-Hf-Nb (Figure 1b1) and Ti-Zr-Hf-Ta (Figure 1b2) ground phase diagrams, only HfZr exists as a ground-state compound. The formation energy of HfZr with an ordered HCP structure is extremely small at -0.096 kJ / mol, and it was not considered realistic for this compound to form.
[0043] In the Ti-Zr-Hf-Mo phase diagram (Figure 1b1), Ti3Mo and the Raves phases ZrMo2 and HfMo2 were present. The formation energies of these compounds were -12.9 kJ / mol, -12.4 kJ / mol, and -15.5 kJ / mol for Ti3Mo, ZrMo2, and HfMo2, respectively. Figure 1b suggests that in the Ti-Zr-Hf-Nb-Ta-Mo alloy system, solid solution formation may be inhibited by intermetallic compounds involving Mo. Thermodynamic calculations have been reported to be effective in predicting the constituent phases of biological HEA.
[0044] Figure 1c shows the equilibrium calculation results using FactSage version 7.3 and SGTE2017 (http: / / www.factsage.com / (accessed 4 March 2020)). No significant difference was observed between the liquidus temperature (TL) estimated by thermodynamic calculations and the composition-averaged melting point for any of the alloys. Regardless of the alloy composition, a BCC single phase existed as a stable phase below the solidus temperature (TS). The temperature difference between TL and TS, that is, the solid-liquid coexistence region, had a smaller temperature range for TZHNTM-Eq (Figure 1c1) than for TZHNTM-X (X = 1, 2, 3) (Figures 1c1-1c3). Below the BCC phase decomposition temperature (TD), the BCC single-phase state was no longer thermodynamically stable.
[0045] The TD of TZHNTM-Eq (Figure 1c1) was higher than that of TZHNTM-X (X = 1, 2, 3) (Figures 1c1-1c3). For all TZHNTM-X (X = Eq, 1, 2, 3) alloys, the HCP phase existed as a stable phase at a temperature considerably lower than TD. The thermodynamic calculation results suggested that the BCC phase was formed by solidification in all TZHNTM-X (X = Eq, 1, 2, 3) alloys.
[0046] Example 3 Next, attempts were made to actually produce ingots using the vacuum arc melting method for various compositions. Arc-melted ingots of TZHNTM-X (X = Eq, 1, 2, 3) alloys were produced from mixtures of pure element starting materials. The cooling rate in the arc melting method is estimated to be approximately 2000 Ks-1, which is about one order of magnitude higher than that of typical die casting, and about three orders of magnitude higher than that of crucible melting and cooling. The microstructure and constituent phases were investigated by XRD (X-ray diffraction), SEM (scanning electron microscopy), and EDS (Energy Dispersive X-ray Spectroscopy).
[0047] The tensile test was performed at room temperature at a strain rate of 1.67×10 -4 s-1 The study was conducted using the following method. The function of the fabricated TZHNTM-X (X = Eq, 1, 2, 3) alloy as a biomaterial was evaluated by analyzing the cell adhesion behavior controlled by molecular-level interactions between the alloy surface and cells. Figure 2 shows the XRD patterns and SEM microstructural observation results for isotope ratio TZHNTM-Eq and TZHNTM-3, a typical example of an asotope ratio alloy. In the XRD pattern shown in Figure 2a, the calculated intensities of Ti3Mo, ZrMo2, and HfMo2 are also shown.
[0048] Here, the calculated intensity was obtained using VESTA (K. Momma, F. Izumi, J. Appl. Crystallogr., 41 (2008) 653-658). The sharp diffraction peaks observed in the isoatomic ratio TZHNTM-Eq were identified as two BCC phases. On the other hand, the sharp diffraction peak of TZHNTM-3 was identified as a single-phase BCC phase. Figure 2b shows the SEM backscattered electron image and the results of EDS elemental mapping focusing on Ti and Zr. In the isoatomic ratio TZHNTM-Eq (Figure 2b, left), dendrites showing white contrast and interdendritic dendritic regions showing gray contrast were observed. The two BCC phases observed in the XRD pattern were thought to correspond to the dendritic BCC phase and the interdendritic dendritic BCC phase. In the non-equal atomic composition ratio TZHNTM-3 (Figure 2b, right), no significant differences in the composition of Ti and Zr were observed between dendrites and between dendrite trees.
[0049] Furthermore, the difference in the degree of segregation between the isoatomic composition ratio TZHNTM-Eq and the non-isoatomic composition ratio TZHNTM-3 was thought to correspond to the temperature difference between TL and TS (i.e., the temperature range of the solid-liquid coexistence region) and the partition coefficient (k) in TL, as predicted by thermodynamic calculations. The partition coefficients of Ti (kTi) and Zr (kZr) in the isoatomic composition ratio TZHNTM-Eq were calculated to be 0.76 and 0.55, respectively. On the other hand, the kTi and kZr of the non-isoatomic composition ratio TZHNTM-3 were calculated to be 0.85 and 0.93, respectively. The kZr in the isoatomic composition ratio TZHNTM-Eq is considerably smaller than 1, unlike the kZr in the non-isoatomic composition ratio TZHNTM-3, which was thought to correspond to the emergence of a large compositional partition. The formation of Mo-related intermetallic compounds was not observed by XRD or SEM in any of the TZHNTM-X (X = Eq, 1, 2, 3) samples.
[0050] Example 4 Next, the results of tensile tests on an alloy in one embodiment of the present invention were examined. Figure 3 shows the results of room-temperature tensile tests on arc-melted ingots with an unequal atomic composition ratio TZHNTM-3. Here, the unequal atomic composition ratio TZHNTM-3 is the alloy that exhibits the lowest values for VEC and Moeq among TZHNTM-X (X = Eq, 1, 2, 3). The yield stress of TZHNTM-3 was approximately 700 MPa, which is higher than that of CP-Ti. This characteristic is similar to the characteristic of Ti-Nb-Ta-Zr-Mo bio-HEA, where the yield stress evaluated by room-temperature compression is higher than that of CP-Ti.
[0051] Example 5 Next, biocompatibility was evaluated in one embodiment of the present invention. Figure 4 shows the biocompatibility evaluation results of arc-melted ingots of an unequal atomic composition ratio Ti28.32Zr28.32Hf28.32Nb6.74Ta6.74Mo1.55 (TZHNTM-3) alloy. The reference materials were SUS-316L stainless steel, Co-Cr-Mo alloy (ASTM F1537-08), and CP-Ti. Figure 4a shows the cell density analyzed based on Giemsa stained images of osteoblasts that adhered to and proliferated on the fabricated alloy surface. Cell adhesion to the material surface is one of the main factors indicating the biocompatibility of the material, and showed a significantly different trend depending on the type of alloy. The biocompatible alloys SUS-316L and Co-Cr-Mo surfaces showed significantly lower cell adhesion numbers compared to CP-Ti and TZHNTM-3 alloys. The CP-Ti and TZHNTM-3 alloys did not show a statistically significant difference in cell count, meaning that the fabricated TZHNTM-3 alloy possesses biocompatibility comparable to that of CP-Ti.
[0052] In addition, focusing on cell morphology, which directly affects the construction of biological tissues and organs, different characteristic cell morphologies were observed depending on the type of substrate material. Figure 4b shows the fluorescence staining images of the cytoskeleton and adhesion plaques of osteoblasts on the surface of the fabricated samples. Osteoblasts on SUS316L and Co-Cr-Mo alloys had poor cytoskeletons and exhibited a small, shrunken cell morphology. On the other hand, on the TZHNTM-3 alloy, cells had abundantly developed actin filaments and exhibited a broadly extended cell morphology. This means that this alloy has the same good cell adhesion properties as pure titanium, which is used in orthopedic and dental implant materials.
[0053] Furthermore, on the fabricated alloy, it can be seen that well-developed adhesion plaques (a group of molecules that control cell adhesion to the metal substrate; difficult to discern in the figure, but the red area in Figure 4 (the colored area labeled "vinculin")) have extended to a size of 5 μm or more. (Adhesion plaques smaller than <5 μm also exist.) Adhesion plaques extending to 5 μm or more are directly involved in bone formation and are expected to actively contribute to the formation of surrounding bone when implants are placed. In addition, on the fabricated alloy, cells form actin filaments (cytoskeletal proteins; difficult to discern in the figure, but the green area in Figure 4 ( The colored area labeled F-actin shows a cell morphology characterized by a network of actin filaments. Actin filaments are fibrous proteins that bind to adhesion plaques and are also linked to the nucleus, which contains genetic information; their development is directly related to cell function. Furthermore, the cells used for biocompatibility evaluation in this study were primary mouse osteoblasts, and because they are primary cells (cells extracted from living organisms), they may contain other cell types (fibroblasts, periosteal cells, osteoclasts, and osteocytes). It is also evident that the adhesion and proliferation of undifferentiated mesenchymal stem cells, which are the origin of osteoblasts, can be used as indicators.
[0054] Example 6 Next, we attempted to create cast and heat-treated alloys as part of one embodiment of the present invention. A Ti28.33Zr28.33Hf28.33Nb6.74Ta6.74Mo1.55 (at%) alloy was obtained by vacuum arc melting. XRD observation of the resulting alloy's crystal structure confirmed that it is a solid solution with a simple structure (a bcc structure in this embodiment), which is the most distinctive feature of HEA (Figure 5).
[0055] The bcc structure was maintained in the obtained alloy even after heat treatment at 1000°C for one week (1273K, 168h). In terms of microstructure, the equiaxed dendritic structure characteristic of high-entropy alloys, as previously reported, was observed in the cast material (Figure 6). Both the cast and heat-treated materials of this alloy were suitable for tensile testing, and their yield stresses reached approximately 700 MPa for the cast material and approximately 1000 MPa for the heat-treated material, which is more than 1.1 times the yield stress of Ti-6Al-4V alloy, currently the most widely used biocompatible metal material (Figure 7). After seeding osteoblasts in these example alloys and culturing them for 24 hours, the cultured cells on each sample were stained with Giemsa dye, and their biocompatibility was examined. As shown in Figure 8, both the cast and heat-treated materials not only exhibited significantly superior biocompatibility compared to SUS316L, Co-Cr-Mo alloy (ASTM F1537-08), but also showed values equivalent to pure titanium, a practical bio-metal material. This demonstrates that the HEA developed in this study possesses high biocompatibility.
[0056] These results indicate that this alloy exhibits extremely low cytotoxicity due to the formation of an oxide film on its surface, supporting the suitability of its constituent elements as biomaterials. Therefore, it was found that the developed TZHNTM alloy exhibits superior biocompatibility to SUS-316L and Co-Cr-Mo alloys, and even possesses biocompatibility comparable to pure titanium, which is commonly used as a biomaterial.
[0057] As described above, we have successfully developed a Ti-Zr-Hf-Nb-Ta-Mo bio-HEA with an unequal atomic composition ratio that is tensile at room temperature and exhibits excellent biocompatibility. In the Ti28.33Zr28.33Hf28.33Nb6.74Ta6.74Mo1.55 (TZHNTM-3) alloy, an arc-melted ingot with a BCC structure free of intermetallic compounds was obtained. The TZHNTM-3 alloy exhibited ductility that allowed for tensile strength at room temperature, and its yield stress was significantly higher than that of CP-Ti. Moeq and VEC proved effective in designing alloys for bio-MEA and bio-HEA with a BCC structure. The TZHNTM-3 alloy showed high biocompatibility comparable to that of CP-Ti. [Industrial applicability]
[0058] The HEA obtained by this invention possesses unprecedented high strength, high ductility, and high biocompatibility, thus creating a new market for biocompatible HEA alloys and generating significant ripple effects across a wide range of industries and product categories.
Claims
1. The alloy is a multi-component system containing titanium, zirconium, niobium, molybdenum, tantalum, and hafnium (excluding tungsten and vanadium), and the alloy is defined as follows: Mo equivalent (where Mo equivalent = [Mo] + 0.26 [Au] + 0.43 [Bi] + 12.62 [Be] + 2.93 [Co] + 1.65 [Cr] + 0.85 [Cu] + 4.17 [Fe] + 0.05 [Hf] + 0.17 [Mg] + 3.28 [Mn] + 0.64 [Nb] + 1.75 [Ni] + 0.23 [Os] + 0.71 [Pd] + 0.64 [Pt] + 0.29 [Pu] + 1.72 [Re] + 2.89 [Rh] + 1.67 [Ru] + The alloy satisfies 0.97[Si] + 0.23[Ta] + 0.32[U] + 0.80[V] + 0.56[W] + 1.13[Y] + 0.16[Zr]) ≥ 13.5, and the alloy is a multicomponent system consisting of a single-phase solid solution, a two-phase solid solution, or a solid solution phase as the main phase, and the alloy satisfies the condition 1.5R ≤ ΔSmix (where R is the gas constant and ΔSmix is the configurational entropy), and is a multicomponent system satisfying -15 ≤ Hmix, 7 ≥ δ, 4.7 ≥ VEC (where Hmix is the mixing enthalpy, δ is the atomic radius ratio factor and VEC is the valence electron concentration), and the alloy has the general formula: (TiZrHf) X (NbTa) Y Mo 100-X-Y A multi-component alloy characterized by the following (where 57.2 ≤ X ≤ 85 and 12.8 ≤ Y ≤ 33.3; the values in parentheses indicate the presence of the element in parentheses).
2. The alloy according to claim 1, characterized in that the alloy includes a BCC structure.
3. A biocompatible material comprising the alloy described in Claim 1 or 2.
4. A method for producing a multi-component alloy according to claim 1 or 2, characterized in that it includes a step of melting the alloy by a method selected from a rapid solidification method, a vacuum arc melting method, a casting method, a melting method, a three-dimensional additive manufacturing method, or a powder metallurgy method.
5. Furthermore, the method according to claim 4, further comprising the step of annealing the alloy.
Citation Information
Patent Citations
Low thermal expansion coefficient NaMxAlySiz high entropy alloy and preparation method thereof
CN104120325A
TiZrNbMoxHfy multi-principal component high temperature alloy and preparation method thereof
CN104213013A
High-melting-point high-entropy alloys and preparation method thereof
CN107267842A
Microalloyed Ti-Zr-Hf-V-Nb-Ta refractory high-entropy alloy and preparation method thereof
CN108220742A
Irradiation-resistant high-entropy alloy and preparation method thereof
CN109666811A